Homozygous hypomorphic BRCA2 variant in primary ovarian insufficiency without cancer or Fanconi anaemia trait. Issue 2 (1st June 2020) - Caburet, Sandrine; Heddar, Abdelkader; Dardillac, Elodie; Creux, Héléne; Lambert, Marie; Messiaen, Sébastien; Tourpin, Sophie; Livera, Gabriel; Lopez, Bernard S; Misrahi, Micheline
Abstract : Background: Primary ovarian insufficiency (POI) affects 1% of women under 40 years and is a public health problem. The genetic causes of POI are highly heterogeneous with isolated or syndromic forms. Recently, variants in genes involved in DNA repair have been shown to cause POI. Notably, syndromic POI with Fanconi anaemia (FA) traits related to biallelic BRCA2 truncated variants has been reported. Here, we report a novel phenotype of isolated POI with a BRCA2 variant in a consanguineous Turkish family. Methods: Exome sequencing (ES) was performed in the patient. We also performed functional studies, including a homologous recombination (HR) test, cell proliferation, radiation-induced RAD51 foci formation assays and chromosome breakage studies in primary and lymphoblastoid immortalised cells. The expression of BRCA2 in human foetal ovaries was studied. Results: ES identified a homozygous missense c.8524C>T/p.R2842C -BRCA2 variant. BRCA2 defects induce cancer predisposition and FA. Remarkably, neither the patient nor her family exhibited somatic pathologies. The patient's cells showed intermediate levels of chromosomal breaks, cell proliferation and radiation-induced RAD51 foci formation compared with controls and FA cells. R2842C-BRCA2 only partially complemented HR efficiency compared with wild type-BRCA2. BRCA2 is expressed in human foetal ovaries in pachytene stage oocytes, when meiotic HR occurs. Conclusion: We describe the functional assessment of a homozygous hypomorphic BRCA2 variant in a patient with POI without cancer or FA trait. Our findings extend the phenotype of BRCA2 biallelic alterations to fully isolated POI. This study has a major impact on the management and genetic counselling of patients with POI.